Impact on inequities in health indicators: Effect of implementing the integrated management of neonatal and childhood illness programme in Haryana, India - Sunita Taneja; Shikhar Bahl; Sarmila Mazumder; Jose Martines; Nita Bhandari; Maharaj Kishan Bhan (Edinburgh University Global Health Society, 2015)
Background: A trial to evaluate the Integrated Management of Neo-natal and Childhood Illness (IMNCI) strategy showed that the intervention resulted in lower infant mortality and improved infant care practices. In this paper, we present the results of a secondary analysis to examine the effect of the IMNCI strategy on inequities in health indicators. Methods: The trial was a cluster-randomized controlled trial in 18 primary health centre areas. For this analysis, the population was divided into subgroups by wealth status (using Principal Component Analysis), religion and caste, education of mother and sex of the infant. Multiple linear regression analysis was used to examine inequity gradients in neonatal and post-neonatal mortality, care practices and care seeking, and the differences in these gradients between intervention and control clusters. Findings: Inequity in post-neonatal infant mortality by wealth status was lower in the intervention as compared to control clusters (adjusted difference in gradients 2.2 per 1000, 95% confidence interval (CI) 0 to 4.4 per 1000, P=0.053). The intervention had no effect on inequities in neonatal mortality. The intervention resulted in a larger effect on breastfeeding within one hour of birth in poorer families (difference in inequity gradients 3.0%, CI 1.5 to 4.5, P<0.001), in lower caste and minorities families, and in infants of mothers with fewer years of schooling. The intervention also reduced gender inequity in care seeking for severe neonatal illness from an appropriate provider (difference in inequity gradients 9.3%, CI 0.4 to 18.2 ,P=0.042). Conclusions: Implementation of IMNCI reduced inequities in post-neonatal mortality, and newborn care practices (particularly starting breastfeeding within an hour of birth) and health care-seeking for severe illness. In spite of the intervention substantial inequities remained in the intervention group and therefore further efforts to ensure that health programs reach the vulnerable population subgroups are required.